The direct and indirect effect of the COVID-19 pandemic on patients with cardiomyopathy. (14th October 2021) - Hammersley, D J; Buchan, R J; Mach, L; Jones, R E; Halliday, B P; Prasad, S K; Roberts, A; Ware, J S
Abstract: Background: The disease-specific impact of COVID-19 on different cardiac conditions requires further investigation. Whilst direct effects are observed for those infected with SARS-CoV-2, the indirect effects of the pandemic arising from interruption to clinical care may represent a further source of morbidity and mortality. Purpose: To evaluate the direct and indirect effects of the COVID-19 pandemic on patients with dilated cardiomyopathy (DCM) and hypertrophic cardiomyopathy (HCM). Methods: (i) Patients with DCM or HCM previously recruited to a single centre registry were studied using NHS Spine Summary Care Records, hospital records and patient questionnaires. The primary outcome was test-proven COVID-19 infection. Secondary outcomes were the proportion of COVID-19 cases requiring hospitalisation and the proportion of subjects advised to shield. Outcomes were compared with published UK COVID-19 statistics. (ii) The Heart Hive COVID-19 study is an international online prospective observational cohort study. Subjects registered on an online platform with cardiomyopathy or without heart disease (controls) were invited to enrol. Enrolled subjects complete online surveys, adapted from a WHO Survey tool for behavioural insights on COVID-19. Results: (i) Of 1236 eligible patients in our registry (703 DCM, 533 HCM), 13 (1.1%) had tested positive for COVID-19 compared to 1.6% in the UK population (p=0.14) up to 2nd November 2020, a higher proportion of whom required hospitalisation compared with the UK population (53.8% vs 16.5%, p=0.002). More patients with cardiomyopathy in our registry were advised to shield than in the UK population (21.9% vs 6.8%, p<0.ehab724.17361, Fig. 1). (ii) Of 207 subjects enrolled in the Heart Hive COVID-19 study (131 cardiomyopathy, 76 controls), more patients with cardiomyopathy felt their physical health had deteriorated due to the pandemic than controls (32.3% vs 13.2%, p=0.0042) despite only 4.6% reporting COVID-19 symptoms. Of those with cardiomyopathy, 38 (29.0%) reported a rescheduled clinic visit, 21 (16.0%) a cancelled clinic visit, 51 (38.9%) had missed investigations, 10 (7.6%) had cancelled/postponed procedures, 7 (5.3%) had missed medication doses due to the pandemic and 53 (40.4%) felt their health needs could not be met by telemedicine (Fig. 2). The psychological impact of the pandemic was comparable between cardiomyopathy patients and controls. Conclusions: Patients with cardiomyopathy in our registry were not at a greater risk of testing positive for COVID-19 than the UK population, but a higher proportion of those that tested positive required hospitalisation. Many more patients with cardiomyopathy reported a subjective deterioration in physical health than had experienced COVID-19 symptoms, inferring a significant contribution of the indirect effects of the pandemic. Our findings have implications for both the health needs of these patients and the reorganisation of clinical services to meet these. FUNDunding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): The Wellcome Trust, Medical Research Council (UK)